Neuronal Cell-Intrinsic Defects in Mouse Models of Down Syndrome - Chiotto, Alessandra Maria Adelaide; Migliorero, Martina; Pallavicini, Gianmarco; Bianchi, Federico Tommaso; Gai, Marta; Di Cunto, Ferdinando; Berto, Gaia Elena (Frontiers in Neuroscience, 2019)
Down Syndrome (DS) is the most common genetic disorder associated with intellectual disability (ID). Excitatory neurons of DS patients and mouse models show decreased size of dendritic field and reduction of spine density. Whether these defects are caused by cell autonomous alterations or by abnormal multicellular circuitry is still unknown. In this work, we explored this issue by culturing cortical neurons obtained from two mouse models of DS: the widely used Ts65Dn and the less characterized Ts2Cje. We observed that, in the in vitro conditions, axon specification and elongation, as well as dendritogenesis, take place without evident abnormalities, indicating that the initial phases of neuronal differentiation do not suffer from the presence of an imbalanced genetic dosage. Conversely, our analysis highlighted differences between trisomic and euploid neurons in terms of reduction of spine density, in accordance with in vivo data obtained by other groups, proposing the presence of a cell-intrinsic malfunction. This work suggests that the characteristic morphological defects of DS neurons are likely to be caused by the possible combination of cell-intrinsic defects together with cell-extrinsic cues. Additionally, our data support the possibility of using the more sustainable line Ts2Cje as a standard model for the study of DS.